Radical‐Mediated Fluoroalkylations. Issue 1 (26th October 2015) - Cho, Eun Jin
Abstract: Recently, the development of eco‐friendly radical processes has become of great interest in synthetic chemistry. In particular, visible‐light photocatalysis has drawn tremendous attention for its environmental compatibility and versatility in promoting many synthetically important reactions. In addition, inorganic electrides as electron donors have emerged as new eco‐friendly tools for radical transformations since they consist of non‐toxic and naturally abundant main metals such as calcium. The design of new fluoroalkylation reactions has benefited greatly from recent advances in visible‐light photocatalysis and the chemistry of inorganic electrides. Since adding fluoroalkyl groups can dramatically change the physical and chemical properties of organic compounds, using these processes to promote eco‐friendly radical fluoroalkylations will have a major impact in areas such as pharmaceuticals, agrochemicals, and material sciences. This Personal Account reviews radical‐mediated fluoroalkylations, such as trifluoromethylations and difluoroalkylations, recently developed in our laboratory. Abstract : Methods have been developed for the installation of trifluoromethyl and difluoroalkyl groups into a variety of organic molecules. The use of eco‐friendly resources, such as visible light and non‐toxic inorganic electrides, and non‐functionalized molecules as substrates, as well as their atom‐economical nature, makes these reactions ideal examples of green chemistry.